PEMANFAATAN INSTAGRAM TERHADAP PENINGKATAN KEMAMPUAN MEMBACA DALAM PEMBELAJARAN BAHASA INDONESIA - Sri Winda; Dela Amalia; Nurlisa Nurlisa (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
The purpose of this study was to examine the potential and usefulness of the Instagram application as an innovative learning tool that can improve students' academic reading skills in Indonesian language courses. In this digital age, students' dependence on social media provides a significant opportunity to integrate technology into formal teaching methods. This study used a qualitative approach with a literature review method, where data was obtained through critical analysis of numerous journals and relevant literature. The findings of the study indicate that Instagram features have different strategic roles: the feed feature is most effective in helping students understand the structure of scientific texts; Instagram Stories helps increase reflective interaction; IGTV provides support in understanding complex texts; while Reels serves to practice the skill of summarizing information concisely. Overall, Instagram is effective in providing stimulation, mediation, and information. The conclusion of this study is that planned use of Instagram not only increases reading interest and digital literacy but also strengthens students' critical thinking skills through a digital platform that is relevant to their daily lives.